Prevalence of metabolic comorbidities in obese children - Jacob, Ambili Susan; G., Reetha (International Journal of Contemporary Pediatrics, 2017)
Background: Obesity has been defined as an excess of body weight due to chronic caloric imbalance with more calories consumed than expended each day. Objective of present study was to determine the prevalence of metabolic co morbidities in obese children in our local population Methods: Hospital based cross-sectional study conducted in the endocrinology clinic of a tertiary care hospital for a period of 1 year. Obese children attending the clinic during the study period were included. Their clinical and metabolic parameters including hypertension, lipid profile, diabetes and thyroid status were evaluated. Results: A total of 65 children were included in the final analysis. Dyslipidemia was seen in 63% of the study subjects with high LDL cholesterol being the most frequent lipid abnormality. Conclusions: The prevalence of dyslipidemia among obese children in our population was similar to that in other parts of the country, though we got a higher prevalence of LDL cholesterol.